Advances in understanding the reproductive toxicity of endocrine-disrupting chemicals in women - Wang, Jinguang; Zhao, Chunwu; Feng, Jie; Sun, Pingping; Zhang, Yuhua; Han, Ailing; Zhang, Yuemin; Ma, Huagang (Frontiers in Cell and Developmental Biology, 2024)
Recently, there has been a noticeable increase in disorders of the female reproductive system, accompanied by a rise in adverse pregnancy outcomes. This trend is increasingly being linked to environmental pollution, particularly through the lens of Endocrine Disrupting Chemicals (EDCs). These external agents disrupt natural processes of hormones, including synthesis, metabolism, secretion, transport, binding, as well as elimination. These disruptions can significantly impair human reproductive functions. A wealth of animal studies and epidemiological research indicates that exposure to toxic environmental factors can interfere with the endocrine system's normal functioning, resulting in negative reproductive outcomes. However, the mechanisms of these adverse effects are largely unknown. This work reviews the reproductive toxicity of five major environmental EDCs-Bisphenol A (BPA), Phthalates (PAEs), Triclocarban (TCC), Triclosan (TCS), and Disinfection Byproducts (DBPs)-to lay a foundational theoretical basis for further toxicological study of EDCs. Additionally, it aims to spark advancements in the prevention and treatment of female reproductive toxicity caused by these chemicals.